The Optimization Strategies of Student Knowledge and Behavior in Plastic Waste Management of Semarang State University - Widyawati, Shaiba Ayu; Prajanti, Sucihatiningsih Dian Wiska; Hardati, Puji (Universitas Negeri Semarang, 2021)
The objective of this paper is to analyze the strategies that have been carried out by UNNES on student knowledge understanding and behavior in plastic waste management and prioritize optimization strategies of student knowledge and behavior in plastic waste management in the Semarang State University environment. This research was designed descriptively by using a qualitative analysis approach using key persons consisting of Head of the UPT BANGVASI UNNES, Head of the UNNES Household Section, Academics who are experts in the conservation field, and UNNES students. Furthermore, the analytical tool used to determine the optimization strategy in this research used the Analytical Hierarchy Process (AHP). The location of this research was on the Semarang State University Campus, which consists of the Sekaran Campus and the UNNES Postgraduate Program Campus. The results of the research showed that (1) The first criteria that are most prioritized in the strategy to optimize student knowledge and behavior in plastic waste management are facilities and infrastructure with a weight value of 45.8% or 0.458; (2) The second priority criterion is HR with a weight value of 41.6% or 0.416; (3) The last strategic priority criterion is policy criterion with a value of 12% or 0.126.